Shape-shifting: Reimaging mothering and mother-being - Venter, Marguerite (Michaelis School of Fine Art, 2024)
Based on my lived experience, this body of work reimages the representation of mothering, motherbeing and the space in between through a visual exploration within photography. The overlooked space between mothering and mother-being renders it invisible as the two positions are frequently conflated. My work reassesses and redresses the representation of the mother and the concept of mothering within the context of art. Finally, the practical work and accompanying research challenge the modest, marginalised and repressed place that mothering (and mother-artists) has occupied within fine art. The role of the mother and the concept of motherhood are burdened with expectations, presumption, convention, tradition, judgement and discrimination. Within the context of art, the Madonna and Child trope remains the most instantly summoned and enduring visual standard to address mothering. My project attempts to widen the narrow aperture through which the contemporary mother and mothering is viewed. It would be presumptuous to assume that my voice is representative of the experience of all mothers everywhere. For the purposes of this body of work my own lived experience–being the mother in a middle-class, single-parent household while studying, classified as divorced, South African, white, born at the cusp of Generation X and Y (millennial)–serves as the context from which I approach mothering.1 It is important to emphasise the distinction between mothering and mother-being and acknowledge the fluxive space between—wherein independence and being depended on, meet, clash, reconcile and coexist. I consider mothering to be the active, ongoing process of caring for and raising one's child(ren): caring for their physical, emotional, intellectual, spiritual and social needs. Mothering also includes leading by example (actions, words, beliefs). Motherbeing revolves around the mother reconciling her pre- and post-child identity with her mothering identity; the personal experience of being a mother in relation to other identities within oneself (e.g. being an artist and/or a student—as in my case—in relation to one's existence as a mother).